Penambahan Upper Limb Tension Test (UlTT) Terhadap Aktivitas Fungsional Pada Cervical Root Syndrome (CRS) - Noviana, Harfika, Dwi Rosella Komala Sari, S.Fis, M.Fis, Dipl. Cidesco (2016)
Background : cervical root syndrome is a collection of symptoms due to an emphasis on the spinal nerves that are often caused by the degeneration of the vertebrae and intervertebral discs in the neck. Upper limb tension test is one of the ways to reduce adhesions that exist around the nerve to nerve itself. So, it can increase the nerve spasticity. Objectives : this research aims to determine the addition upper limb tension test fot the functional activity in cervical root syndrome. Research Methods : this research uses quasi experimental. The pre and post study design test use control design with the treatment group is given the addition neurodynamic mobilization by upper limb tension test on conventional therapy, while in the control group is given conventional therapy. The sampling technique uses consecutive sampling with neck disability index measuring instrument. This research is obtained before and after the treatment program completed. This research is conducted 2 times in a week for 4 weeks. Result : the result shown that control group gets P value =0.027 (p>0.005) while the treatment group gets P value = 0.026 (p>0.005) and the influence of different test after the treatment between the two group get P value =0.626 (p<0.005). Conclution : conventional therapy and neurodynamic mobilization in patients with cervical root syndrome have influence to the functional activity, however there are no significant differences. Keywords : Upper Limb Tension Test, Functional Activity, Cervical Root Syndrome